Enterovirus infection in the Socialist Republic of Vietnam - L. N. Golitsyna; T. T.T. Nguyen; N. I. Romanenkova; M. T. Luong; L. T. Vu; O. I. Kanaeva; M. A. Bichurina; N. A. Novikova (Инфекция и иммунитет, 2019)
Human enterovirus infections comprise a group of infectious diseases caused by viruses of Enterovirus A-D species (genus Enterovirus, family Picornaviridae). Enterovirus infections can vary in clinical manifestations and severity, from asymptomatic infection to serious multisystem diseases. During evolution, enterovirus strains with increased neurovirulence or atypical pathogenicity may emerge exhibiting an epidemic potential. Recently, outbreaks of enterovirus infection with an increased rate of neurological manifestations, a significant percentage of severe cases and lethal outcomes have been observed worldwide, which were associated with enteroviruses EV-A71, EV-D68 etc. The World Health Organization has included EV-A71 and EV-D68 enterovirus infection together with some other dangerous viral diseases considered for inclusion in the List of Blueprint Priority Diseases. In connection with this, global enterovirus surveillance is important for controlling emergence and spread of epidemic enterovirus variants, prediction of establishing epidemic situation, timely conduction of preventive measures and vaccine development. A growing multi-field cooperation between Russia and Vietnam leads to increased two-way population migration, which actualizes scientific and practical collaboration in surveillance and control of infectious disease spread, including enterovirus infection. Currently, epidemiological surveillance of enterovirus infection in Vietnam is based on monitoring hand, foot and mouth disease (HFMD) rate, laboratory diagnostics of enterovirus infection and identification of enterovirus strains, mainly detected in severe patients. In 2001–2016, 34 non-polio virus types were identified in patients with enterovirus infection, largely represented by viruses EV-A71, CVA6, CVA10, and CVA16. Moreover, the peak incidence of enterovirus infection and related mortality rate were associated with the increased activity of EV-A71 virus. In Vietnam, EVA71 enterovirus of genotypes C1, C4, C5 and B5 circulated at different times. Over the last years, a new pandemic genotype virus CVA6 has been dominating as a causative agent of enterovirus infection in Vietnam as well as the majority of other countries. The data on phylogenetic relation between Vietnamese epidemic EV-A71 and CVA6 strains allowed to find that they underwent multiple betweencountry spreads, whereas their subsequent in-country dissemination resulted in 2011–2012 enterovirus outbreak and sustained high-level HFMD morbidity.